Nanowire Electrodes for Advanced Lithium Batteries - Huang, Lei; Wei, Qiulong; Sun, Ruimin; Mai, Liqiang (Frontiers in Energy Research, 2014)
Since the commercialization of lithium ion batteries (LIBs) in the past two decades, rechargeable LIBs have become widespread power sources for portable devices used in daily life. However, current demands require higher energy density and power density of batteries. The electrochemical energy storage performance of LIBs could be improved by applying nanomaterial electrodes, but their fast capacity fading is still one of the key limitations and the mechanism needs to be clearly understood. Single nanowire electrode devices are considered as a versatile platform for in situ probing the direct relationship between electrical transport, structure change, and other properties of the single nanowire electrode along with the charge/discharge process. The results indicate the conductivity decrease of the nanowire electrode and the structural disorder/destruction during electrochemical reactions which limit the cycling performance of LIBs. Based on the in situ observations, some feasible structure architecture strategies, including prelithiation, coaxial structure, nanowire arrays and hierarchical structure architecture, are proposed and utilized to restrain the conductivity decrease and structural disorder/destruction. Further, the applications of nanowire electrodes in some “beyond Li-ion” batteries, such as Li-S and Li-air battery, are also described.